Số hóa với hệ thống Kirtas - Đỗ, Như Thơ (Cục Thông tin khoa học và công nghệ quốc gia, 2023)
Presents the experience of the National Agency for Scientific and Technological Information (NASATI) in exploitation of Kirtas equipment for digitalizing documents.